KONSTRUKSI IDENTITAS SUPORTER SEPAKBOLA DI INDONESIA - Yovita Sabarina Sitepu Fransiska Desiana Setyaningsih (PERSPEKTIF, 2016)
Focus of this research is to describe how the member of Persija FC’s supporter constructing their identities before and after they become the member of The Jakmania. Case study method is used with multi case-single level analysis design. It is found that, in each of three informants’ self, the changing of identities are really happened. One of the changing identities about for example is their social status after they have joined with The Jakmania. In the beginning, before they join with The Jakmania, people did not pay attention to them. It was because their low socio-economic status. Now, after joined The Jakmania, they have their own ingroup that strengthen their individual identity.